Pertumbuhan Caisim (Brassica juncea (L.) Czern.) pada Beberapa Konsentrasi Larutan Hidroponik Sistem NFT - Adinda Nurul Huda Manurung; Fitri Yulianti (Universitas Gunadarma, 2017)
Chinese mustard is one of the most important vegetables of the Brassica (Brassicaceae) genus with high consumption in the world. Mustards content of selected compounds, calcium, magnesium, potassium, sodium, vitamin C, carotene, and lutein. Mustard is one of the plants that can be cultivated on hydroponics. The NFT system is a type of hydroponic system that placing the plant on an oblique irrigation channel. The important thing in hydroponic fertilization was to ensure the concentration of nutrient solution that suits the plant and its life cycle. The purpose of this research was to determine the best consentration for the growth Chinese mustard on in NFT system. This research was conducted at F6 Campus Gunadarma University located at Depok (±115 m above sea level) from March to April 2017. The treatment was arranged in Completely Randomized Design with five replications. The treatment was concentration of hydroponic solution i.e. 1050 ppm, 1200 ppm and 1400 ppm. Treatment of difference of nutrient solution concentration had no significant effect on plant height, number of leaf, root length, number of root and fresh harvest weight. The best concentration of nutrient solution in this study was 1050 ppm nutrition solution. The concentration of 1050 ppm is a better treatment than the 1200 ppm and 1400 ppm nutrient treatment because it is more efficient in the use of Vegemix A Hydrofarm and Vegemix B Hydrofarm solution.